Vorming tot Bevrijding. Jaarverslag…. (Hasselt : Vorming tot Bevrijding, 1987)
Fonds Suzan Daniel (FSD)
Periodiciteit : jaarlijks
Redactie : Lazarijstraat 6, 3500 Hasselt – Albertlaan 27, 3220 Aarschot
Nederlands
Periodiek